2021
DOI: 10.21608/jappmu.2021.153597
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Pathotyping of Infectious Bursal Disease Virus (IBDV) from Field Outbreaks among Chickens in Egypt

Abstract: Infectious bursal disease (IBD) is a main health problem causing considerable economic losses in poultry flocks in Egypt. Throughout 2018-2019, bursae samples were assembled from different chicken's farms localized in four Egyptian governorates (Giza, Bani-Suif, Fayoum and Qalubia). The samples collected from farms recorded history of Infectious Bursal Disease (IBD) signs such as: sudden mortalities; depression; diarrhea; and hemorrhages on bursal tissues, leg and breast muscles. For virus isolation, the colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Regarding ICPI, the result showed that isolate from Giza was velogenic with ICPI of 1.652 and isolates from Cairo and Menoufiya governorates were velogenic with ICPI of 1.601 and 1.601 respectively. This result agreed with that obtained by Nabila et al (2014).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Regarding ICPI, the result showed that isolate from Giza was velogenic with ICPI of 1.652 and isolates from Cairo and Menoufiya governorates were velogenic with ICPI of 1.601 and 1.601 respectively. This result agreed with that obtained by Nabila et al (2014).…”
Section: Discussionsupporting
confidence: 93%
“…In Egypt, outbreaks of NDV are still frequently occurring in vaccinated poultry flocks, despite the intensive vaccination programs (Mohamed et al, 2011 andNabila et al, 2014). The main objective of the present work was identification of circulating NDV in Egyptian chicken and development of control methods for infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aside from characterizing field strains from a molecular perspective, it is essential to understand their pathogenic features and ensure that the currently enacted control measures are effective. A wealth of data has been produced in the Egyptian context on the pathogenicity of locally circulating very virulent IBDVs, which consistently cause typical IBD signs and lesions with high mortality rates [59][60][61], and on the protection induced by different live [61], vector [62,63] and immune complex [64] vaccines, which appears adequate. Novel variant IBDVs, on the other hand, are associated with subclinical infections with severe bursal atrophy and lymphocyte depletion [16,46,65,66].…”
Section: Discussionmentioning
confidence: 99%
“…NDV was initially identified in Egypt in 1948 (Daubney & Mansy, 1948). Since then, Egypt has been regarded as an endemic country for ND (Nabila et al, 2014). NDV has three strains: velogenic (viscerotropic and neurotropic), mesogenic, and lentogenic.…”
Section: Pathologymentioning
confidence: 99%